2013
DOI: 10.1002/qua.24580
|View full text |Cite
|
Sign up to set email alerts
|

Odd‐hydrogen: An account on electronic structure, kinetics, and role of water in mediating reactions with atmospheric ozone. Just a catalyst or far beyond?

Abstract: Odd‐hydrogen (any hydrogen‐oxygen radical containing but a single hydrogen atom) plays a key role in atmospheric chemistry, particularly in the chemistry of ozone. Notable is also the role played by water in atmospheric and environmental chemistry. Without attempting a broad coverage, the present survey focuses on the electronic structure and dynamics of odd‐hydrogen and related water‐mediated complexes with impact in atmospheric chemistry, with emphasis on systems studied at the author's laboratory. Review or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 317 publications
(584 reference statements)
0
17
0
Order By: Relevance
“…We explore whether ammonia can accelerate the OH + H 2 SO 4 reaction and a single water molecule can promote the NH 2 + H 2 SO 4 reaction. Some theoretical and experimental investigations have demonstrated that a single water molecule can affect the rate constants of gas‐phase reactions in the atmosphere . In addition, the competition mechanisms between OH + NH 3 and OH + H 2 SO 4 are also considered, which may be of great interest because previous investigations have demonstrated that the similar reaction mechanisms play an important role in the atmospheric oxidation of HNO 3 .…”
Section: Introductionmentioning
confidence: 74%
“…We explore whether ammonia can accelerate the OH + H 2 SO 4 reaction and a single water molecule can promote the NH 2 + H 2 SO 4 reaction. Some theoretical and experimental investigations have demonstrated that a single water molecule can affect the rate constants of gas‐phase reactions in the atmosphere . In addition, the competition mechanisms between OH + NH 3 and OH + H 2 SO 4 are also considered, which may be of great interest because previous investigations have demonstrated that the similar reaction mechanisms play an important role in the atmospheric oxidation of HNO 3 .…”
Section: Introductionmentioning
confidence: 74%
“…In a global chemical-transport-model-based study, the deposition velocity was considered to be similar to formic acid, yielding a HNCO lifetime of 1-3 d (over the ocean) to 1-2 weeks (over vegetation) (Young et al, 2012). The UV absorption for HNCO is only reported at wavelengths < 262 nm, and photolysis is mostly reported for energies at wavelengths below 240 nm by excitation to the first singlet excited states, forming H + NCO or NH + CO (Keller-Rudek et al, 2013;Okabe, 1970;Uno et al, 1990;Vatsa and Volpp, 2001). In the troposphere photolysis occurs only at the UV absorption wavelength band > 290 nm due to filtering of shorter-wavelength radiation (Hofzumahaus et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the traditional cycloaddition channels, three further channels were found, corresponding to Habstraction, forming HO 3 + NCO, oxygen transfer to the N-atom, forming ON(H)CO + 1 O 2 , and addition on the C-and N-atom, forming HN(OO)C(O)O. The HO 3 product radical is known to be only weakly bonded by 2.94 kcal mol -1 , falling apart to OH + O 2 (Bartlett et al, 2019;Le Picard et al, 2010;Varandas, 2014).…”
Section: Hnco + Omentioning
confidence: 99%